‘Pulp Methodism’ Revisited: The Literature and Significance of Silas and Joseph Hocking - Wellings, Martin (Studies in church history, 2012)
Writing pseudonymously in the New Age in February 1909, Arnold Bennett, acerbic chronicler of Edwardian chapel culture, deplored the lack of proper bookshops in English provincial towns. A substantial manufacturing community, he claimed, might be served only by a stationers shop, offering ‘Tennyson in gilt. Volumes of the Temple Classics or Everyman. Hymn books, Bibles. The latest cheap Shakespeare. Of new books no example, except the brothers Hocking.’ Bennett’s lament was an unintended compliment to the ubiquity of the novels of Silas and Joseph Hocking, brothers whose literary careers spanned more than half a century, generating almost two hundred novels and innumerable serials and short stories. Silas Hocking (1850-1935), whose first book was published in 1878 and last in 1934, has been described as the most popular novelist of the late nineteenth century. By 1900 his sales already exceeded one million volumes. The career of Joseph Hocking (1860-1937) was slightly shorter, stretching from 1887 to 1936, but his output was equally impressive. The Hockings’ works have attracted interest principally among scholars of Cornish life and culture. It will be argued here, however, that they have significance for the history of late Victorian and Edwardian Nonconformity, both reflecting and reinforcing the attitudes, beliefs and prejudices of their large and appreciative readership.